Population Structure of Macrobrachium rosenbergii (de Man, 1879) at Batang Kerang floosplain, Balai Ringin, Sarawak - Che Nurul Ashikin, binti Che Mat Noor (Universiti Malaysia Sarawak (UNIMAS), 2014)
A study of population structure of Macrobrachium rosenbergii was carried out at Batang Kerang floodplain, Balai Ringin, Serian, Sarawak from October 2013 until March 2014. A total 289 individuals of M. rosenbergii were caught during this study using ‘selambau’. Higher number of individuals M. rosenbergii were caught in January. The number of unberried M. rosenbergii was higher compared to berried M. rosenbergii. The water qualities of water body in December (wet season) and March (dry season) are identified by measuring and comparing results of physico-chemical parameters namely pH, temperature, dissolved oxygen, turbidity, depth, ammonia-nitrogen and nitrate-nitrogen with the results of physico-chemical parameters in March. The majority population of M. rosenbergii at Batang Kerang floodplain had total length between 10.10 cm to 15.00 cm and weighed between 15.01 g to 30.00 g, indicating the majority population of M. rosenbergii was small. However, population of M. rosenbergii in December was smaller compared to population of M. rosenbergii in October and January. Generally, majority length-weight relationship of M. rosenbergii in Batang Kerang floodplain shows a positive strong correlation (P < 0.05), meaning that the increasing of total length correlated with the increasing of weight of M. rosenbergii even though their size is small.